Operational evaluation of the deployment of Malaria/CRP Duo and Dengue Duo rapid diagnostic tests for the management of febrile illness by village malaria workers in rural Cambodia - Marc T. Visser; Dysoley Lek; Bipin Adhikari; Arjun Chandna; Moul Vanna; Sam Ol; Voeurng Bunreth; Chan Davoeung; Yok Sovann; Dafne Umans; Yoel Lubell; Rusheng Chew; et al. (BMC Infectious Diseases)
Abstract Introduction The decline in malaria cases in Cambodia has led to a relative increase in non-malarial febrile illness. In rural Cambodia, village malaria workers (VMWs) provide early diagnosis and treatment for malaria, but their role and relevance are diminishing as malaria cases decline. Expanding VMW roles would ensure continued utilisation of their services until malaria elimination is achieved and strengthen community health services. Methods A mixed methods operational research study was implemented to evaluate the use of two combination-RDTs (combo-RDTs) as an expansion of the VMW role, enabling VMWs in Cambodia to test for diseases other than malaria for the first time. VMWs in 78 villages in Battambang and Pailin Provinces were trained and provided with either a Malaria/CRP Duo or Dengue Duo RDT to assess febrile patients. Data were collected on VMW consultations, and combo-RDT usage and results. Focus group discussions (FGDs) and competency assessments of combo-RDT usage were conducted with VMWs. The main objectives were to determine whether VMWs could perform these combo-RDTs correctly and follow management algorithms, and whether deployment had an impact on VMW consultation rates. Perspectives concerning role expansion and the feasibility of conducting additional tests were also explored. Results Between June 2022, and May 2023, a total of 2,425 febrile patients were assessed with either a Malaria/CRP Duo or Dengue Duo RDT. Active dengue infection (NS1- and/or IgM-positive) was identified in 1.2% (11/915) of patients. Positive CRP results (> 20 mg/L) were found for 3.2% (48/1,510) of patients. Following deployment, there was an immediate mean increase of 4.4 VMW consultations per month, from 9.0 to 13.4 (p < 0.01). Competency assessments revealed that some VMWs had difficulty performing the Dengue Duo RDT, particularly in collecting the correct blood volume. This limitation may have led to false-negative dengue NS1 results. VMWs and community members were keen to broaden the skills and responsibilities of VMWs. Conclusions Deploying combo-RDTs to VMWs led to a higher utilization of their services. Difficulties performing some aspects of the Dengue Duo RDT, low positivity rates, and a lack of actionable outcomes within the existing context of VMW services suggest that alternative interventions may be better suited for VMW role expansion at this time. Overall, VMWs and community members were receptive to the expansion of the VMW role for a wider range of diseases other than malaria.